Characteristics of Stratum Structure and Fracture Evolution in Stratified Mining of Shallow Buried High-Gas-Thick Coal Seam by Similarity Simulation. (10th November 2021) - Guangpeng, Qin; Jing, Cao; Chao, Wang; Shuo, Wu; Minghua, Zhai
Abstract : The stratified mining of super thick coal seam is a process of repeated disturbance of the top roof, especially in the lower stratification, the upper complex rock layer has a greater settlement space, resulting in great changes in the strata structure and fissure distribution. The main coal seam thickness of Rujigou Coal Mine exceeds 20 m, due to the high gas content of the coal seam, it is prone to spontaneous combustion, and the stratified mining method is adopted. When a small-size section coal pillar (less than 10 m) is used, the complex rock structure evolution and fissure development characteristics during the stratified mining of shallow buried thick coal seam will directly affect the movement of gas transportation between the working face and the goaf and will directly affect the safety of the working face. Taking Rujigou coal mine as engineering background, this paper analyzes the breaking structure, fracture development, and evolution law of overlying strata in different layers and different sections of coal seam when the buried depth is shallow, and the extra-thick coal seam is stratified mining. The results show that in the process of stratified mining, the overlying strata break, in addition to the whole trapezoidal failure structure, will also form a local F type fracture structure, and with the stratified downward mining, the F type fracture structure will continue to move up and disappear until it is compacted. The "V" type and "U" type subsidence characteristics of different strata overburden are presented after mining in stratified working face of extra-thick coal seam, and the subsidence amount is approximately symmetrical distribution along the middle line of goaf. In the mining process of the lower part of the layer, the end broken rock block is easy to slip along the hinge point by the hinged rock beam structure, and the sliding instability occurs. In the process of stratified mining of ultrathick coal seam, the main fissure of overburden is mainly longitudinal fissure, and it is very easy to form through with the upper layer and will finally connect with the surface under the condition of shallow buried depth. The inclined cracks connected with the adjacent goaf are formed above the coal pillar of the section, which becomes the passage of gas migration in the goaf. The research conclusion shows that for the stratified mining of high gas thick coal seam, special attention should be paid to the treatment of the gas on the stratified working face. In addition to the conventional gas treatment measures such as coal seam prepumping, the buried pipe pumping in the mining area can also be adopted, which can effectively reduce the gas concentration of the working surface.